Heart Rate Variability a Cardiac Indicator in Diabetic Autonomic Neuropathy: A Systematic Review - Joel Mukesh Raja; Mary, Annapoorna; Kishore, Arcot (International Journal of Medical Research, 2013)
Background: Cardiac indicator Heart Rate variability (HRV) is a significant sensitive and early predictor, which could be used for early deduction of complications among Diabetes Mellitus patients. Many studies have reported the usefulness of HRV as diagnostic method, however, there is a gap in the literature in the utilization of HRV in the clinical practice in planning, providing, and evaluating quality care for patients with diabetic autonomic neuropathy. Purpose: The purpose of this systematic review it was to review the cardiac indicators of diabetic autonomic neuropathy. Method: A Systematic Review of published clinical research articles from PUBMED data source was performed and the review is organized under method and result section. The research articles were selected for the review with inclusion criteria including clinical research studies, addressing concepts of HRV, diabetes mellitus, and autonomic neuropathy. Conclusion: The review concluded that existing literature support that the HRV is a sensitive cardiac indicator, which may help to predict the cardiac morbidity and mortality among diabetes mellitus patients. HRV may be used as a significant cardiac indicator to predict diabetic autonomic neuropathy. This finding may be useful in the early diagnosis and treatment of complications among patients with diabetes mellitus.